Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4141/cjas2011-030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flaxseed and forage type on carcass and meat quality of finishing cull cows

Abstract: Hernández-Calva, L. M., He, M., Juárez, M., Aalhus, J. L., Dugan, M. E. R. and McAllister, T. A. 2011. Effect of flaxseed and forage type on carcass and meat quality of finishing cull cows. Can. J. Anim. Sci. 91: 613–622. Sixty-two cull cows were fed one of four diets in a 2×2 factorial arrangement, consisting of barley silage or grass hay with or without flaxseed to influence fatty acid composition. After slaughter, carcass grade, meat quality and sensory data were collected. Silage increased live (P=0.002) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
4
5
1
1
Order By: Relevance
“…However, a trend of a lower total area value was noted in the meat of SOY steers (P = 0.08), which is associated with more tender meat. These results were similar to those of Hernández-Calva et al (2011), who found no differences in the values of shear force after supplementing feeds with flax seed in finishing cull cows.…”
Section: Meat Qualitysupporting
confidence: 90%
“…However, a trend of a lower total area value was noted in the meat of SOY steers (P = 0.08), which is associated with more tender meat. These results were similar to those of Hernández-Calva et al (2011), who found no differences in the values of shear force after supplementing feeds with flax seed in finishing cull cows.…”
Section: Meat Qualitysupporting
confidence: 90%
“…However, Non-TMR steaks had significantly lower beef flavor intensity (-0.62 panel units, P < 0.01) and greater off-flavor intensity (lower off-flavor values, -1.30 panel units, P < 0.01) than those from TMR steers. This agrees with previous studies (Hernández-Calva et al, 2011;LaBrune et al, 2008), who found an increase of off-flavor intensity in beef when feeding flaxseed. Conversely, McNiven et al (2011) reported no effect of feeding flaxseed on freshly cooked beef off-flavor.…”
Section: Resultssupporting
confidence: 83%
“…In contrast to the results of Price et al [ 61 ] in young bulls and steers, in our study, the combination of a higher hay percentage in the fattening diet and heavier slaughter weight did not lead to a lower dressing%. As demonstrated in many studies, the fattening diet composition could have no impact on the dressing% in cattle [ 55 , 57 , 62 , 63 ]. It could explain the few differences observed between the four rearing managements applied during the heifers’ whole life considered in our study.…”
Section: Discussionmentioning
confidence: 99%